School Management and Character Formation for High-Achieving Students at MI Darul Hikmah Menganti - Mahmuda; Nina Oktarina (Educational Management, 2026)
This study examines the school management strategies implemented at MI Darul Hikmah Menganti in shaping the character of high-achieving students. Supported by management theory, character education, and the Indonesian Pancasila Student Profile framework, this study aims to analyze how the functions of planning, organizing, executing, and evaluating (POAC) are used to strengthen students' academic and non-academic achievements. Using a qualitative case study approach, data were collected through in-depth interviews, documentation, and achievement records from teachers, administrators, students, and parents. Findings show that the school instills a culture of achievement through its motto “A Thousand Students, A Thousand Champions,” integrates a Quran memorization program, establishes a structured extracurricular system, encourages collaborative involvement of teachers and parents, and conducts continuous evaluation through character reports and performance competitions. This study concludes that effective management strategies significantly improve students' spiritual, moral, academic, and achievement-oriented character. Recommendations include strengthening digital-based evaluation tools, expanding parent partnership programs, and extending the talent development model to other schools.